A Bibliographic Analysis of Conflict and Social Entrepreneurship Studies Throughout History - hasyim lalhakim, muhammad; Yuliarto Nugroho, Bernardus; Fitriani, Rachma (International Journal Labs, 2025)
Conflict engagement and social entrepreneurship are currently being studied by several scholars. Although social entrepreneurs often struggle to distinguish between creating social and financial value, they become embedded agents through their entrepreneurial agency as they work with various stakeholders, including individuals, organizations, and communities, to achieve common goals. The purpose of this paper is to provide a comprehensive overview of numerous research projects related to conflict engagement and social entrepreneurship. Utilizing a tool called VOSViewer, we present the results of our bibliometric analysis, which includes an examination of publications from the Scopus database spanning from 2008 to 2024. The analysis reveals 93 documents, comprising 64 journal articles, 18 books, 6 conference proceedings, and 5 book series. The highest number of publications was recorded in 2024, with 14 papers released. Among these, the most cited document, authored by Tobias et al. (2013), has been cited 198 times. The United States emerged as the leading country in this field, with 25 publications and 543 citations, highlighting the growing importance of social entrepreneurship in addressing conflict and promoting peace. This study offers a valuable bibliometric overview of the research trends and influence in the field, providing a foundation for future studies.